2019
DOI: 10.1002/anie.201814193
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Visible‐Light‐Mediated Formation of 3‐Cyclopropylquinolones by Triplet‐Sensitized Deracemization

Abstract: 3-Allyl-substituted quinolones undergo at ripletsensitized di-p-methane rearrangement reaction to the corresponding 3-cyclopropylquinolones upon irradiation with visible light (l = 420 nm). Ac hiral hydrogen-bonding sensitizer (10 mol %) was shown to promote the reaction enantioselectively (88-96 %y ield, 32-55 %e e). Surprisingly,i tw as found that the enantiodifferentiation does not occur at the state of initial product formation but that it is the result of aderacemization event. The individual parameters t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
58
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 50 publications
1
58
0
6
Order By: Relevance
“…Shortly after, the same group extended this strategy to the deracemization of 3‐cyclopropylquinolones, which were formed in situ from 3‐allyl‐substituted quinolones 3 in a di‐π‐methane rearrangement reaction, using the enantiomer of thioxanthone 2 as the chiral photosensitizer (Scheme ) . Control experiments confirmed that the enantioselectivity was not determined by the initial cyclopropane formation but by a subsequent photochemical cyclopropane deracemization process.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shortly after, the same group extended this strategy to the deracemization of 3‐cyclopropylquinolones, which were formed in situ from 3‐allyl‐substituted quinolones 3 in a di‐π‐methane rearrangement reaction, using the enantiomer of thioxanthone 2 as the chiral photosensitizer (Scheme ) . Control experiments confirmed that the enantioselectivity was not determined by the initial cyclopropane formation but by a subsequent photochemical cyclopropane deracemization process.…”
Section: Methodsmentioning
confidence: 99%
“…[6,7] In general, three types of interaction between the photoexcited species and the reactants are involved in visible-light photocatalysis:e nergy transfer (E n T), electron transfer (ET), and hydrogen atom transfer (HAT). Gratifyingly,b yt aking full advantage of these interaction modes,r ecent studies from the groups of Bach [9,10] and Miller and Knowles [11] have achieved the selective deracemization of chiral compounds with central or axial chirality under visible-light irradiation. Herein, we highlight these works and discuss the opportunities that Scheme 1.…”
mentioning
confidence: 99%
“…Die gleiche Arbeitsgruppe erweiterte kurze Zeit später diese Strategie auf die Deracemisierung von 3‐Cyclopropylchinolonen, die über eine Di‐π‐methan‐Umlagerungsreaktion in situ aus den 3‐Allyl‐substituierten Chinolonen 3 gebildet werden, mit dem Enantiomer von Thioxanthon 2 als chiralem Photosensibilisator (Schema ) . Kontrollexperimente bestätigten, dass die Enantioselektivität nicht durch die anfängliche Cyclopropanbildung bestimmt wurde, sondern durch einen sich anschließenden photochemischen Cyclopropan‐Deracemisierungsprozess.…”
Section: Methodsunclassified
“…[6,7] Im Allgemeinen finden bei der Photokatalyse mit sichtbarem Licht drei Arten von Wechselwirkungen zwischen den photoangeregten Spezies und den Reaktanden statt:E nergietransfer (E n T), Elektronentransfer (ET) und Wasserstoffatomtransfer (HAT). Erfreulicherweise gelang es nun den Gruppen von Bach [9,10] sowie Miller und Knowles [11] in [12] Andererseits sind axial-chirale Allene konfigurativ instabil wenn sie in den Triplettzustand angeregt werden, da die beiden Enantiomere über ein achirales planares diradikalisches Intermediat ineinander umgewandelt werden kçnnen (siehe unten). [13] Diese Eigenschaft macht Allene jedoch zu geeigneten Substraten fürd ie photochemische Deracemisierung.T atsächlich wurde ein Enantiomerenüberschuss von 3.4 %( ee)b eobachtet, wenn Penta-2,3-dien in Gegenwart einer stçchiometrischen Menge eines chiralen Sensibilisators mit UV-Licht bestrahlt wurde.…”
Section: Methodsunclassified
See 1 more Smart Citation